Migration, regionalization, citizenship: comparing canada and europe - Sarkowsky, Katja; Schultze, Rainer-Olaf; Schwarze, Sabine (Politikwissenschaftliche Paperbacks, Studien und Texte zu den politischen Problemfeldern und Wandlungstendenzen westlicher Industriegesellschaften, 2015)
From the perspectives of the political sciences as well as literature and language studies, this volume looks comparatively at Canadian and European constellations of cultural and linguistic diversity. By so doing, it takes Canada as exemplary for the effects of transnationalization, regionalization, and cultural and linguistic diversification on notions of citizenship and processes of identity formation.   Content • Migration, Transnationalism, and Labour • Citizenship, Multiculturalism, and Representation • Regionalism, Language, and Identity   Target Groups • Researchers and students in the field of English and Romance cultural studies and linguistics as well as social sciences • Practitioners of English and Romance cultural studies   The Editors Prof. Dr. Katja Sarkowsky holds the Chair of American Studies at the Westfälische Wilhelms-Universität Münster. Prof. Dr. em. Rainer-Olaf Schultze was Professor for Political Science and Managing Director of the Institute for Canadian Studies at the University of Augsburg (until 2011). Prof. Dr. Sabine Schwarze holds the Chair of Romance Linguistics at the University of Augsburg.